ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Hesty, Ratih; Sutrisno, Sutrisno; Pratiwi, Lindah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This research aims to determine the effect of compensation, workload, and work stress on employee performance with job satisfaction as an intervening variable. The sampling technique in this research used the total sample.The results of this research show that compensation affects employee performance with a P-value value (0.000). workload does not affect employee performance with a P-value value (0.563). Work stress does not affect employee performance with a P-value value of (0.468). Compensation influences job satisfaction with a P-value (0.004). Workload has no effect on job satisfaction with a P-value value (0.058). Job stress influences job satisfaction with a P-value (0.013). Job satisfaction influences employee performance with a P-value (0.001). Compensation affects employee performance which is mediated by job satisfaction with a P-value value (0.039). Workload does not affect employee performance which is mediated by job satisfaction with a P-Value value (0.072). Job stress affects employee performance which is mediated by job satisfaction with a P-value value (0.046).